Identification of a Six-lncRNA Signature With Prognostic Value for Breast Cancer Patients - Zhao, Erjie; Lan, Yujia; Quan, Fei; Zhu, Xiaojing; A, Suru; Wan, Linyun; Xu, Jinyuan; Hu, Jing (Frontiers in Genetics, 2020)
Breast cancer is the most common cancer and the major cause of death in women. Long noncoding RNAs (lncRNAs) are emerging as key regulators and have been implicated in carcinogenesis and prognosis. In this study, we aimed to develop a lncRNA signature of BRCA patients to improve risk stratification. In the training cohort (GSE21653, n = 232), 17 lncRNAs were identified by univariate Cox proportional hazards regression, which were significantly associated with patients’ survival. The LASSO-penalized Cox proportional hazards regression analysis was used to identify a six-lncRNA signature. According to the median of signature risk score, the patients were divided into a high-risk group and a low-risk group with significant disease-free survival differences in training cohort. The similar phenomenon was observed in validation cohorts (GSE42568, n = 101; GSE20711, n = 87). The six-lncRNA signature remained as independent prognostic factors after adjusting for clinical factors in these two cohorts. Furthermore, this signature significantly predicted the survival of grade III patients and ER-positive patients. Furthermore, in another cohort (GSE19615, n = 115), the low-risk patients treated with tamoxifen therapy had longer DFS than those without therapy. Overall, the six-lncRNA signature can be a potentially prognostic tool to predict disease-free survival of patients and benefits of tamoxifen treatment in breast cancer, which is helpful to guide individualized treatments for BRCA patients.